THE EFFECT OF MS PHOTO STORY 3 ON STUDENTS' SPEAKING ACHIEVEMENT - Dila Charisma; Khomarudin (Universitas Kuningan, 2019)
Technology information and communication now takes the best attention from educators. It plays to be good or even better media in teaching and leraning process. Therefore, prospective English teachers should have good skill in creating new class atmosphere toward technology. They need to use technology to be the suitable media in learning English, especially speaking, since speaking is considered to be one of difficult skill. Ms Photo Story 3 is one of many computer applications that can be used as a media in teaching speaking. This present study focuses on the effect of Ms Photo Story 3 in improving prospective English teachers' speaking and the response of using Ms Photo Story 3 in learning English, especially speaking. Experiment with one group, pre-test, treatment and post-test were employed in this study. The results showed that there are increasing prospective English teachers' scores. It can be seen from the comparison score of pretest and posttest. Furthemore, the result from the questionaire revealed that the participants' response after using Ms Photo Story 3 in speaking class is categorized good. Thus, it can be concluded that Ms Photo Story 3 is effective in giving prospective English teachers experiences to create digital speaking.